The Effect of Experience, E-Trust, Perceived Ease of Use, Technology Readiness, and Perceived Enjoyment on the Purchase Decision of Virtual Game Items (A Study on Users of the Grand Theft Auto VI/GTA VI Game Application) - Amma Fazizah; Eko Agus Alfianto; Muhammad Sulhan (Journal of Economic, Management and Entrepreneurship, 2026)
This study aims to analyze the effects of Experience, E-Trust, Perceived Ease of Use, Technology Readiness, and Perceived Enjoyment on the purchase intention of virtual items among users of the GTA V game application in the Facebook GTA VI Indonesia community. This study employed a quantitative approach with an explanatory research design. Primary data were collected through questionnaires, while the sample was determined using purposive sampling. Based on the Slovin formula with a population of 87,300 users, 398 respondents were selected who met the research criteria, namely users who had played GTA VI within the last six months and had previously purchased virtual items. The data were analyzed using multiple linear regression with the assistance of SPSS. The partial test results indicate that Experience has no significant effect on Purchase Decision (t = 1.525; p = 0.101), while E-Trust has a positive and significant effect (t = 2.779; p = 0.002). Perceived Ease of Use has a significant effect (t = 2.879; p < 0.003), while Technology Readiness (t = 3.224; p = 0.001) and Perceived Enjoyment (t = 7.705; p < 0.001) have positive and significant effects. Simultaneously, the five variables have a significant effect on Purchase Decision, with an adjusted R² of 0,470.